Fundamental rights adjudication in the Central European region - Sándor, Lénárd (Comparative Constitutionalism in Central Europe: Analysis on Certain Central and Eastern European Countries, 2022)
The protection and adjudication of fundamental rights have been playing an increasingly important role in the legal systems of Western countries since the end of World War II. However, the early origins of fundamental rights go back well over two millennia. The theories of fundamental rights first appeared in the legal system of the ancient empires. The Code of Hammurabi in the ancient Babylon articulated the first requirement for fair trial as it provided that unfair judges be fined and removed from their positions. The Torah first revealed by Moses (c.1304–1237 bce) also contained provisions on the prohibition of false witnesses. The first human rights document has been claimed to be the Charter of Cyrus from 539 bce because the word ‘rights’ specifically appears therein. However, the modern concept of human rights that the state is for the people and not the other way around began to take root at the end of the eighteenth century. After their first appearances, the historical development of fundamental rights has taken place either through an organic and gradual process or as a result of independence or revolutionary movements. Different phases of this development can be distinguished, which involved the rights of the noble, limitation of the power of absolute monarchies, and individual and collective rights. The development in England is an example of the former where the power of monarchs were bound by law and rights as early as the adoption of the Magna Charta Libertatum in 1215. The subsequently created Petition of Right (1628), Habeas Corpus Act (1679) and Bill of Rights (1689) are gradual fulfillment of the historic path of rights. In the CEE region, Hungary underwent similar organic development with the adoption of the ‘Aranybulla’ in 1222, which set constitutional limits on the power of the monarch and granted rights to the Hungarian nobility. In contrast to this type of gradual expansion, in other countries, the recognition and codification of fundamental rights were the result of cataclysmic events such as an independence movement or revolutionary war, e.g. in France or in the United States. It must also be mentioned that while national constitutions served as the cradle of the modern conception of fundamental rights, they began to enjoy the protection of international law with the adoption of the UN Charter (1945) along with the Universal Declaration of Human Rights (1948). This so-called ‘normative revolution’ marked a major turning point in the development of both human rights law and international public law. However, the universality of human rights, instead of standardising rights, would allow – and also require from – states to implement these rights according to the national, historical, cultural and religious traditions of their respective communities. Consequently, the primary places of nurturing and protecting fundamental rights remain within the states and local communities. Accordingly, not only individual rights in the abstract but also the institutions and control mechanisms that serve to protect them are embedded and shaped by the various histories, traditions and legal cultures of the states. In numerous countries – such as the United States of America, Australia, Japan or the Scandinavian countries in Europe – ordinary courts are empowered to conduct a ‘judicial review’ to protect rights enshrined in the constitution. This type of ‘judicial review’ was first applied by the Supreme Court of the United States of America in the famous case of Marbury v. Madison in 1803 as part of the system of checks and balances, whereby the judicial branch serves as a check on the legislative as well as on the executive. In other countries – such as those in continental Europe – a separate and centralised institution – the Constitutional Court – is responsible for conducting fundamental rights adjudication. This chapter aims to provide a comparative analysis on the historical path, major institutions and mechanisms of fundamental rights adjudication in countries of the CEE region. To this end, it first outlines the concept, function, characteristics as well as the institutions of fundamental rights adjudication along with the aspects of limitation of fundamental rights (Section II). Then, it turns to the countries of the Central European region. This chapter aspires to provide a comparative overview about the unique characteristics of the systems of each country’s fundamental rights’ adjudication and concludes with a short assessment (Section III).KEYWORDS: fundamental rights, protection and limitation of fundamental rights judicial review, centralized and decentralized constitutional review, Ombudsmen-like institutions